Pengaruh Motivasi, Kepuasan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Kospin Jasa Cabang Surakarta - Iis Nur Hidayati; Sutarno (Teewan Journal Solutions, 2025)
The phenomenon of this study, the suboptimal performance of employees at Kospin Jasa Surakarta Branch, is marked by a decrease in the results of employee performance assessments in 2024 compared to the previous year. The purpose of this study is to analyze the significance of the influence of motivation on the performance of employees of Kospin Jasa Surakarta Branch, to analyze the significance of the influence of job satisfaction on the performance of employees of Kospin Jasa Surakarta Branch, to analyze the significance of the influence of the work environment on the performance of employees of Kospin Jasa Surakarta Branch. The population of this study was all employees of Kospin Jasa Surakarta Branch, with a total of 71 people. This study used saturated sampling, namely taking all members of the population as samples. The data collection technique used a questionnaire assessed on a 5-point Likert scale. The data analysis technique used multiple linear regression analysis. The results of the analysis show that (1) Motivation has a significant effect on the performance of employees of Kospin Jasa Surakarta Branch, indicated by the p value (0.002) <0.05, thus hypothesis 1 is proven. (2) Job satisfaction has a significant effect on employee performance at Kospin Jasa Surakarta Branch, indicated by p value (0.000) < 0.05, thus hypothesis 2 is proven. (3) Work environment has a significant effect on employee performance at Kospin Jasa Surakarta Branch, indicated by p value (0.021) < 0.05, thus hypothesis 3 is proven.